E-learning and the science of instruction : proven guidelines for consumers and designers of multimedia learning - Clark, Ruth Colvin; Mayer, Richard E., 1947- (New Jersey Wiley, 2016)
"The essential e-learning design manual, updated with the latest research, design principles, and examples e-Learning and the Science of Instruction is the ultimate handbook for evidence-based e-learning design. Since the first edition of this book, e-learning has grown to account for at least 40% of all training delivery media. However, digital courses often fail to reach their potential for learning effectiveness and efficiency. This guide provides research-based guidelines on how best to present content with text, graphics, and audio as well as the conditions under which those guidelines are most effective. This updated fourth edition describes the guidelines, psychology, and applications for ways to improve learning through personalization techniques, coherence, animations, and a new chapter on evidence-based game design. The chapter on the Cognitive Theory of Multimedia Learning introduces three forms of cognitive load which are revisited throughout each chapter as the psychological basis for chapter principles. A new chapter on engagement in learning lays the groundwork for in-depth reviews of how to leverage worked examples, practice, online collaboration, and learner control to optimize learning. The updated instructor's materials include a syllabus, assignments, storyboard projects, and test items that you can adapt to your own course schedule and students. Co-authored by the most productive instructional research scientist in the world, Dr. Richard E Mayer, this book distills copious e-learning research into a practical manual for improving learning through optimal design and delivery. Get up to date on the latest e-learning research Adopt best practices for communicating information effectively Use evidence-based techniques to engage your learners Replace popular instructional ideas, such as learning styles with evidence-based guidelines Apply evidence-based design techniques to optimize learning games e-Learning continues to grow as an alternative or adjunct to the classroom, and correspondingly, has become a focus among researchers in learning-related fields. New findings from research laboratories can inform the design and development of e-learning. However, much of this research published in technical journals is inaccessible to those who actually design e-learning material. By collecting the latest evidence into a single volume and translating the theoretical into the practical, e-Learning and the Science of Instruction has become an essential resource for consumers and designers of multimedia learning"--
"e-Learning has continued to grow as an alternative to classroom instruction, most measurably notably in increased use of synchronous e-learning technology. Organizations are looking for ways to save travel costs and decrease worker time away from the job. At the same time, instructional professionals recognize that investments made in learning environments that fail to build knowledge and skills aligned to operational goals are wasted regardless of media of delivery. Additionally, there is a growing body of basic research on instructional methods in e-learning that remains largely inaccessible to practitioners as it is published in journals they don't read, written in language they don't understand, discussed at conferences they don't attend, and are not contextualized with relevant examples. e-Learning has continued to grow as an alternative to classroom instruction, most measurably notably in increased use of synchronous e-learning technology. Organizations are looking for ways to save travel costs and decrease worker time away from the job. At the same time, instructional professionals recognize that investments made in learning environments that fail to build knowledge and skills aligned to operational goals are wasted regardless of media of delivery. Additionally, there is a growing body of basic research on instructional methods in e-learning that remains largely inaccessible to practitioners as it is published in journals they don't read, written in language they don't understand, discussed at conferences they don't attend, and are not contextualized with relevant examples"--
Machine generated contents note: Acknowledgments Introduction 1. E-Learning: Promise and Pitfalls Chapter Summary What Is e-Learning? Is e-Learning Better? The Promise of e-Learning The Pitfalls of e-Learning e-Learning Architectures What is Effective e-Coruseware? Learning in e-Learning What to Look for in e-Learning 2. How Do People Learning from E-Courses? Chapter Summary How Do People Learn? Managing Limited Cognitive Resources During Learning How e-Lessons Affect Human Learning? What to Look for in e-Learning 3. Evidence-based Practice Chapter Summary What is Evidence-based Practice? Three Approaches to Research on Instructional Effectiveness What to Look for in Experimental Comparisons How to Interpret Research Statistics How Can You Identify Relevant Research? Boundary Conditions in Experimental Comparisons Practical Versus Theoretical Research What to Look for in e-Learning 4. Applying the Multimedia Principle: Use Words and Graphics rather than Words Alone Chapter Summary Do Visuals Make a Difference? Multimedia Principle: Include Both Words and Graphics Some Ways to Use Graphics to Promote Learning Psychological Reasons for the Multimedia Principle Evidence for Using Words and Pictures The Multimedia Principle Works Best for Novices Should You Change Static Illustrations into Animations? What to Look for in e-Learning 5. Applying the Contiguity Principle: Align Words to Corrresponding Graphics Chapter Summary Principle 1: Place Printed Words Near Corresponding Graphics Psychological Reasons for Principle 1 Evidence for Principle 1 Principle 2: Synchronize Spoken Words with Corresponding Graphics Psychological Reasons for Principle 2 Evidence for Principle 2 What to Look for in e-Learning 6. Applying the Modality Principle: Present Words as Audio Narration Rather than On-screen Text Chapter Summary Modality Principle: Present Words as Speech Rather than On-screen Text Limitations to the Modality Principle Psychological Reasons for the Modality Principle Evidence for Using Spoken Rather than Printed Text When the Modality Principle Applies What to Look for in e-Learning 7. Applying the Redundancy Principle: Explain Visuals with Words in Audio OR Text but Not Both Chapter Summary Principle 1: Do Not Add On-screen Text to Narrated Graphics Psychological Reasons for the Redundancy Principle Evidence for Omitting Redundant On-screen Text Principle 2: Consider Adding On-screen Text to Narration in Special Situations Psychological Reasons for Exceptions to the Redundancy Principle Evidence for Including Redundant On-screen Text What to Look for in e-Learning 8. Applying the Coherence Principle: Adding Extra Material Can Hurt Learning Chapter Summary Principle 1: Avoid e-Lessons with Extraneous Words Multimedia Principle: Include Both Words and Graphics Psychological Reasons to Avoid Extraneous Words in e-Learning Evidence for Omitting Extraneous Words Added for Interest Evidence for Omitting Extraneous Words Added to Expand on Key Ideas Evidence for Omitting Extraneous Words Added for Technical Depth Principle 2: Avoid e-Lessons with Extraneous Graphics Psychological Reasons to Avoid Extraneous Graphics in e-Learning Evidence for Omitting Extraneous Graphics Added for Interest Evidence for Using Simpler Visuals Can Interesting Graphics Ever Be Helpful? Principle 3: Avoid e-Lessons with Extraneous Audio Psychological Reasons to Avoid Extraneous Audio in e-Learning Evidence for Omitting Extraneous Audio What to Look for in e-Learning 9. Applying the Personalization and Embodiment Principles: Use Conversational Style, Polite Wording, Human Voice, and Virtual Coaches Chapter Summary Personalization Principle: Use Conversational Rather than Formal Style, Polite Wording Rather than Direct Wording and Human Voice Rather than Machine Voice Psychological Reasons for the Personalization Principle Promote Personalization through Conversational Style Promote Personalization through Polite Speech Promote Personalization through Voice Quality Embodiment Principle: Use Effect On-screen Coaches to Promote Learning Implications for e-Learning What to Look for in e-Learning 10. Applying the Segmenting and Pretraining Principles: Managing Complexity by Breaking a Lesson into Parts Chapter Summary Segmenting Principle: Break a Continuous Lesson into Bite-size Segments Psychological Reasons for the Segmenting Principle Evidence for Breaking a Continuous Lesson into Bite-Size Segments Pretraining Principle: Ensure that Learners Know the Names and Characteristics of Key Concepts Psychological Reasons for the Pretraining Principle Evidence for Providing Pretraining in Key Concepts What to Look for in E-Learning 11. Engagement in E-Learning Chapter Summary What Is Engagement? When Behavioral Engagement Impedes Learning Engagement that Leads to Generative Processing A New View of Engagement What to Look for in E-Learning 12. Leveraging Examples in E-Learning Chapter Summary What Are Worked Examples? The Psychology of Worked Examples Evidence for Benefits of Worked Examples Principles to Optimize Benefits of Worked Examples Principle 1: Provide Worked Examples in Lieu of Problem Assignments when the Essential Load of the Lesson is High Principle 2: Fade from Worked Examples to Problems Principle 3: Promote Self-Explanations Principle 4: Include Instructional Explanations of Worked Examples in Some Situations Principle 5: Apply Multimedia Principles to Examples Principle 6: Support Learning Transfer Design Guidelines for Far Transfer Worked Examples What to Look for in E-Learning 13. Does Practice Make Perfect? Chapter Summary What is Practice in E-Learning? Is Practice a Good Investment? Principle 1: Add Sufficient Practice Interaction to E-Learning to Achieve the Objective Principle 2: Mirror the Job Principle 3: Provide Effective Feedback Principle 4: Distribute and Mix Practice among Learning Events Principle 5: Apply Multimedia Principles What to Look for in e-Learning 14. Learning Together Virtually Chapter Summary What is Collaborative Learning? What is Computer-Supported Collaborative Learning (CSCL)? Principle 1: Consider Collaborative Assignments for Challenging Tasks Principle 2: Optimize Group Size, Composition, and Interdependence Principle 3: Match Synchronous and Asynchronous Assignments to the Collaborative Goal Principle 4: Use Collaborative Tool Features that Optimize Team Processes and Products Principle 5: Maximize Social Presence in Online Collaborative Environments Principle 6: Use Structured Collaboration Processes to Optimize Team Outcomes What to Look for in e-Learning 15. Who's In Control? Guidelines for E-Learning Navigation Chapter Summary Learner Control Versus Program Control Do Learners Make Good Instructional Decisions? Principle 1: Give Experienced Learners Control Principle 2: Make Important Instructional Events the Default Principle 3: Consider Alternative Forms of Learner Control Principle 4: Give Pacing Control to All Learners Principle 5: Offer Navigational Support in Hypermedia Environments The Bottom Line What to Look for in E-Learning 16. E-Learning to Build Thinking Skills Chapter Summary What are Thinking Skills? Can Thinking Skills be Trained? Principle 1: Focus on Explicit Teaching of Job-Relevant Thinking Skills Principle 2: Design Lessons around Authentic Work Tasks or Problems Evidence for Problem-Focused Instruction Principle 3: Define Job-Specific Thinking Processes What to Look for in E-Learning 17. Learning with Computer Games Chapter Summary Do Games Have a Place in the Serious Business of Training? Which Features Improve a Game's Effectiveness? Does Game Playing Improve Cognitive Skills? Are Games More Effective than Conventional Media? What to Look for in E-Learning 18. Applying the Guidelines Chapter Summary Applying Evidence-based Guidelines to E-Courses E-Learning Guidelines Checklist Review of Sample 1: Excel for Small Business Review of Sample 2: Synchronous Excel Lesson Review of Sample 3: Automotive Troubleshooting Simulation Reflections on Past Predictions Beyond 2016 in Multimedia Research In Conclusion References Glossary List of Tables and Figures Name Index Subject Index About the Authors Wiley Publication Guide .
Revised edition of the authors' E-learning and the science of instruction, 2011.
Includes bibliographical references and index.
Keywords: Business education -- Computer-assisted instruction; BUSINESS & ECONOMICS / Human Resources & Personnel Management